2010
DOI: 10.1521/ijct.2010.3.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning and Anxiety in School Age Children: The Mediating Role of Control Cognitions

Abstract: As a test of the cognitive vulnerability model proposed by Chorpita and Barlow, the present study examined the mediating role of control beliefs on the relationship between family functioning and childhood anxiety. The sample was composed of 147 children aged 7-14 years old. Participant's anxiety levels, family functioning, and perceived control over events was hypothesized to mediate over outcomes in the environment and over their feelings of anxiety, were assessed. Partial support was obtained for Chorpita a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…The results of this study are reinforced by research conducted in New York on children where family dysfunction is significantly associated with high anxiety in children (McGinn et al, 2010).…”
Section: Resultssupporting
confidence: 51%
“…The results of this study are reinforced by research conducted in New York on children where family dysfunction is significantly associated with high anxiety in children (McGinn et al, 2010).…”
Section: Resultssupporting
confidence: 51%
“…However, in this study we did not examine the potential role of locus of control, leaving the question ''why, or how, does family enmeshment impact child BIS sensitivity (and subsequently, anxiety)'' largely unexplained. McGinn et al (2010) have shown that dysfunctional parenting enhances children's susceptibility to anxiety through the mediating role of an external locus of control, and found that children's external locus of control mediated the relationship between family environment characterized by control and child's negative affect. Another group of investigators found that adolescents' feelings of ''identity threat'' (i.e., a belief that one's developing individuality is being threatened) mediated the negative relationship between family enmeshment and well-being, corroborating the above-mentioned findings and further suggesting that the negative implications of enmeshment can be explained largely through its effect on an individual's feelings of autonomy (Manzi et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In testing the aforementioned model, found that children's external locus of control (a perception of diminished control over one's environment) mediates the relationship between family environment characterized by control and child's negative affect. In a similar study, McGinn et al (2010) found that dysfunctional parenting enhances children's susceptibility to anxiety through the mediating role of an external locus of control. These results suggest that overcontrolled children do not learn to feel mastery over their environment and, as a result, come to exhibit fear and anxiety.…”
Section: Introductionmentioning
confidence: 87%
“…Research has also been conducted to investigate cognitive vulnerability factors in the etiology and maintenance of anxiety disorders (e.g., McGinn et al 2005McGinn et al , 2010Riskind and Williams 2005;Riskind et al 2013). Emerging research has focused on testing specific cognitive vulnerability models of panic disorder (PD; e.g., Bentley et al 2013;Gregor and Zvolensky 2008;Li and Zinbarg 2007;Schmidt et al 2006Schmidt et al , 2010Teachman 2005) although some previous studies examining specificity have failed to observe a link between panic disorder patients and individuals with other anxiety disorders (Hofmann et al 2000).…”
Section: Introductionmentioning
confidence: 99%